Evaluación de los mecanismos de participación ciudadana en la toma de decisiones del GAD del Cantón Tosagua periodo 2013-2017. - Vera Zambrano, Jefferson Dario (2018)
The Republic of Ecuador Constitution establishes that citizen participation is a right of all citizens, who can be participants in the decision making of municipal entities, for this reason the main objective of the research was to evaluate the level of citizen participation in the administrative management of the Autonomous Decentralized Government of Tosagua canton for the determination of the incidence degree within the period 2013-2017, in order to comply with the research development three phases were carried out in the methodological development, in the first the public regulatory policies of the Autonomous Decentralized Government of the Tosagua canton, comparing them with the laws that promote citizen participation and in this way verify if they were applied, in the second stage the mechanisms for citizen participation were determined, and two investigation techniques were executed, such as the interview with director of Department of Citizen Participation and Social Control, Engineer Paul Pasquel, based on this, a survey was carried out to the civil society of the canton, with the purpose of gathering pertinent information to determine the citizen participation mechanisms that the municipal entity applies. In the last phase of this research, improvement activities were proposed in relation to the shortcomings found in the application of these mechanisms, in addition to socializing them with the director of the department in question and thus integrating the public into the public management carried out by part of the GAD Tosagua.